Prevalence of Modiﬁable Cardiovascular Disease Risk Factors among Cardiac Patients who were Enrolled on Cardiac Rehabilitation Programme for Secondary Cardiac Prevention in a Local Heart Centre in Malaysia - Chai, Chau Chung; Leong, Be Kim; Liew, Lin Kiat; Chow, Kok Cheow; Kevin Wong Wu, Kein (Hong Kong College of Cardiology, 2023)
Introduction: One of the important goals of cardiac rehabilitation programme (CRP) is secondary cardiac prevention through managing modiﬁable cardiovascular (CVD) risk factors among cardiac patients. There were limited local studies on the prevalence of modiﬁable CVD risk factors among cardiac patients who were enrolled on CRP for planning and allocation of resources in resource-limited settings of local CRP in Malaysia.